2006
DOI: 10.1093/jnci/djj103
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Primary Cutaneous Melanoma and Clinical Outcome

Abstract: We identified 254 genes whose expression was associated with metastatic dissemination of cutaneous melanomas. These genes may shed light on the molecular mechanisms underlying poor prognosis in melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
424
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 456 publications
(459 citation statements)
references
References 36 publications
24
424
1
5
Order By: Relevance
“…To understand melanoma progression, we analysed the gene expression profiles of primary melanoma giving rise to metastasis (M þ ; n ¼ 26) versus the melanoma where no metastasis (MÀ; n ¼ 34) was documented after a 4-year follow-up period (Winnepenninckx et al, 2006) (Supplementary Table 1). By applying searching for a biological interpretation of microarray experiments (SBIME) to the entire data set with Gene Ontology (GO) annotations, we found that two biological processes, that is, replication and repair, are especially overrepresented among the genes that are significantly differentially expressed between M þ and MÀ (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To understand melanoma progression, we analysed the gene expression profiles of primary melanoma giving rise to metastasis (M þ ; n ¼ 26) versus the melanoma where no metastasis (MÀ; n ¼ 34) was documented after a 4-year follow-up period (Winnepenninckx et al, 2006) (Supplementary Table 1). By applying searching for a biological interpretation of microarray experiments (SBIME) to the entire data set with Gene Ontology (GO) annotations, we found that two biological processes, that is, replication and repair, are especially overrepresented among the genes that are significantly differentially expressed between M þ and MÀ (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It shows, moreover, that our experimental approach allows us to detect gene underexpression as well as overexpression between M þ and MÀ tumors. Because the direct relationship between the risk of metastasis and the expression of some replication factors has already been discussed in a previous paper (Winnepenninckx et al, 2006), we are only discussing here the role of DNA repair genes for metastasis formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations